ANALISIS KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI IPA FISIKA GETARAN DAN GELOMBANG DI KELAS VIII SMP NEGERI 4 PEKANBARU - Zalukhu, Desi Natalia; M. Nor, M. Nor; Azhar, Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Science learning especially physics is a learning that educates students to act on the basis of critical thinking and critical scientific behavior. The purpose of this study is to describe the level of critical thinking skills of class VIII students in SMP Negeri 4 Pekanbaru on the science physics material of Vibrations and Waves. The population in this study were class VIII students of SMP Negeri 4 Pekanbaru that has implemented the Curriculum 2013 totaling 343 student. Samples were taken by proportional random sampling so that the sample was 79 student. The instrument was a critical thinking test which is based on the indicator of critical thinking ability which amounted to 24 multiple choice questions. The data were collected by giving a critical thinking ability test to the samples. The data analysis in this study uses descriptive analysis techniques using a percentage scale that provides an overview of the level of students’ critical thinking skills. The results of this study shows information that the average percentage of students’ critical thinking skills in class VIII of SMP Negeri 4 Pekanbaru is 72,96% in the high category of critical thinking skills.Key Words: Critical Thinking Ability, Vibration and Wave Material, Descriptive Analysis.